Innovative Program of Sempu Health Center in Reducing MMR through SAKINA - Susilawati Susilawati (Humanistic Network for Science and Technology (HNST), 2022)
Sempu Health Center in Banyuwangi is a health center that has been able to innovate in order to overcome maternal mortality. Increased case of maternal mortality in 2010 to 2012 prompted the head of Sempu Health Center to innovate with SAKINA program. This program has succeeded in reducing maternal mortality to zero. This study aims to get an overview from the implementation of SAKINA program in reducing the Maternal Mortality Rate (MMR) in Sempu Health Center area. This research used a qualitative case study. The informants in this study were 15 people from both health officers and public who were involved in the activities of the SAKINA program. Based on the results of the research, the SAKINA program is an activity that aims to stop the Maternal and Child Mortality Rate, the innovation is carried out by forming Laskar SAKINA, which is a community assigned with assisting high-risk pregnant women during the pregnancy period. Pregnant women hunters come from vegetable sellers (Mlijo) who are tasked with finding pregnant women in each village within their sales route. In addition, there is a Shelter House which is used to wait for birth in remote areas. The SAKINA program is a form of innovation for increasing community participation in reducing maternal and child mortality. Keywords: MMR; health center; SAKINA; innovative program